GOOD GOVERNANCE TOURISM DALAM PENGELOLAAN OBJEK WISATA BENDUNGAN DESA SUNGAI PAKU KECAMATAN KAMPAR KIRI KABUPATEN KAMPAR TAHUN 2020-2023 - Amelia, Dinda; Handoko, Tito (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Sungai Paku Village has a Dam Tourism Object that has the potential to develop and is known to many people, but the management of the Sungai Paku Dam Tourism Object is not well managed. So, Good Governance Tourism needs to be monitored to find out. In the acknowledgment received from the Chairman of POKDARWIS Natural Tourism Object Sungai Paku Village Dam Mr. Rasyid, he said that the Sungai Paku Village Dam has been inaugurated since 2018 as a tourist attraction, and in 2020 that is when the Covid-19 pandemic occurred, the management of the dam began to be hampered and ended with a drastic decrease in the number of visitors. In addition, the problem phenomenon in this research is that there is a conflict between the agencies that have the authority to build this dam, namely the Public Works and People's Housing Office of the Republic of Indonesia and the Tourism Office. This research intends to find out how the implementation of Good Governance Tourism is not optimal in the management of Sungai Paku Village Dam Tourism Object, Kampar Kiri District, Kampar Regency. Location of Research in the Dam Tourist Object located in Sungai Paku Village, Kampar Kiri District, Kampar Regency. This research uses the theory of Good Governance Tourism proposed by Sunaryo Good Governance Tourism or a good governance of tourism is essentially the coordination and synchronization of programs between existing stakeholders as well as the involvement of synergistic active participation (integrated and mutually reinforcing) between the Government , private sector / tourism industry, and related local communities. The data analysis technique used is Qualitative data analysis is done when the empirical data obtained is qualitative data. The results of the Good Governance Tourism Research in the Management of Tourism Objects Sungai Paku Dam Village Kampar Kiri Subdistrict, Kampar Regency Year 2020-2023 has not gone well, this is because out of 10 indicators only 3 can be implemented. The biggest obstacle that occurs in Good Governance Tourism in the management of Sungai Paku Dam Village Natural Tourism Object, Kampar Kiri District, Kampar Regency Year 2020-2023 is the lack of coordination between the village government and the tourism department in the development of tourist objects. Keywords: Good Governance Tourism - Tourist Object - Sungai Paku Village